Peningkatan Pengetahuan pada Orangtua tentang Gizi Seimbang Anak Usia 3-6 Tahun - Devita, Arleen; Budihartanti Liman, Patricia; Kartini; Yuliana (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
The four-healthy-five-perfect nutritional guidelines that were previously used have changed to the term nutritional pyramid or balanced nutritional stack. Balanced nutrition is one of the most important things that parents must pay attention to in children's growth and development. The long-term impact of poor nutritional status affects the quality of human resources in the future. Therefore, it is necessary for parents to understand through education or increasing knowledge regarding balanced nutritional status so that they can choose food according to their needs to provide balanced nutrition to their children. The counseling activity was carried out on January 27, 2024, which was attended by 13 parents and 8 school teachers. To determine the cognitive changes of participants, we perform pre-test and post-test. The results of the counseling activity showed that participants' knowledge regarding balanced nutrition increased by 23%, and the percentage of correct answers increased from 7.7% to 69.2%. This increased knowledge is expected to enhance understanding and change behaviour of balance nutrition parents towards their children.